PERUBAHAN-PERUBAHAN SOSIAL DAN KEBUDAYAAN YANG TERJADI DI MASYARAKAT PADA MASA SEKARANG - Hutabarat, Dany Try Hutama; Deri, Afif; Indraswary, Apriola Dwi; Salsabila, Jihan; Pasaribu, Liza Umami; Mhd. Irvansyah; Syapiq, Mirza; Saifana, Naila; Pujawati, Sri Anisa; Str, Akmal Satria Alfin (Nusantara Hasana Journal, 2022)
In the modern era like now, people cannot be separated from what is called digital access, often digital access has a major influence on social changes that occur either positively or negatively. Social change is a shift in the structure of society that involves the mindset, attitude and order of social life. Social change is also based on several factors, such as technological advances, intercultural contact, heterogeneous society and many other factors. Social change will always occur in any layer of society so that in responding to the changes that occur we must accept these changes in a positive form and put aside the negative in prder to advance the thoughts of a more open society. This study aims to tell what things affect social change, and what are the positive and negative forms of social change.